Involvement of D2-like dopaminergic receptors in contextual fear conditioning in female rats: influence of estrous cycle - de Oliveira Alves, Camila; Reimer, Adriano Edgar; de Oliveira, Amanda Ribeiro (Frontiers in Behavioral Neuroscience, 2022)
Dopamine has been increasingly recognized as a key neurotransmitter regulating fear/anxiety states. Nevertheless, the influence of sex and estrous cycle differences on the role of dopamine in fear responses needs further investigation. We aimed to evaluate the effects of sulpiride (a dopaminergic D2-like receptor antagonist) on contextual fear conditioning in females while exploring the influence of the estrous cycle. First, using a contextual fear conditioning paradigm, we assessed potential differences in acquisition, expression, and extinction of the conditioned freezing response in male and female (split in proestrus/estrus and metestrus/diestrus) Wistar rats. In a second cohort, we evaluated the effects of sulpiride (20 and 40 mg/kg) on contextual conditioned fear in females during proestrus/estrus and metestrus/diestrus. Potential nonspecific effects were assessed in motor activity assays (catalepsy and open-field tests). No sex differences nor estrous cycle effects on freezing behavior were observed during the fear conditioning phases. Sulpiride reduced freezing expression in female rats. Moreover, females during the proestrus/estrus phases of the estrous cycle were more sensitive to the effects of sulpiride than females in metestrus/diestrus. Sulpiride did not cause motor impairments. Although no sex or estrous cycle differences were observed in basal conditioned fear expression and extinction, estrous cycle seems to influence the effects of D2-like antagonists on contextual fear conditioning.